2017
DOI: 10.2527/jas2017.1488
|View full text |Cite
|
Sign up to set email alerts
|

Management of native warm-season grasses for beef cattle and biomass production in the Mid-South USA

Abstract: Native grasses, such as switchgrass (SG; L.), big bluestem (BB; Vitman), indiangrass (IG; Nash), and eastern gamagrass (EG; [L.] L.) may be capable of providing desirable summer forage for cattle as well as a source of biomass for renewable energy. To evaluate that potential, experiments were conducted at 2 locations in Tennessee comparing weaned beef () steers (268 ± 25 kg initial BW) during early-season grazing (Early; 30 d, typically corresponding to May, followed by postdormancy biomass harvest) and full-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
48
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(67 citation statements)
references
References 0 publications
12
48
4
Order By: Relevance
“…Performance of BBIG during the autumn 2016 drought was poor, resulting in no overall HM differences between BBIG and TF. This contrasts with general observations of increased HM in NWSG and expectations of increased drought performance in C 4 species (Backus et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Performance of BBIG during the autumn 2016 drought was poor, resulting in no overall HM differences between BBIG and TF. This contrasts with general observations of increased HM in NWSG and expectations of increased drought performance in C 4 species (Backus et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Native warm‐season grasses (NWSG) are an alternative forage system (Backus et al., ). These grasses are foundation species to many endangered local ecosystems (Noss, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible solution to this problem is to graze WSGs during summer. While several studies have examined animal performance on WSGs in the southeastern United States, only a few studies have compared the profitability of these forages (Backus et al., ; Burns & Fischer, ; Burns et al., ; Lowe et al., , ). More research is needed to determine WSG species or mixtures that best fit the southeastern United States.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, several studies have analyzed animal performance on WSGs in the southeastern United States, and have found that steers grazing WSGs have positive gains (Backus et al., ; Burns & Fischer, ; Burns, Mochrie, & Timothy, ; Lowe et al., , ). However, only a few existing studies have examined the profitability of grazing WSG.…”
Section: Introductionmentioning
confidence: 99%